2020
DOI: 10.1108/ijlss-05-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating critical failure factors for implementing sustainable lean six sigma framework in manufacturing organization

Abstract: Purpose The purpose of this study is to identify, evaluate and develop a structured model to measure the interrelation between critical failure factors (CFFs) that affects the implementation of the sustainable Lean Six Sigma (SLSS) framework in a manufacturing organization. Further solution approaches have been provided that inhibit those CFFs and help in successful implementation of the framework. Design/methodology/approach To find the interrelation among the selected CFFs and develop a systematic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 80 publications
1
67
0
Order By: Relevance
“…The LM concept we know today consists of indispensable activities applied in the current management and production practices such as automotive, aerospace, furniture manufacturing, textile, process industry and service industry (Kumar and Vinodh, 2020). Due to the foreseen importance of LM, many manufacturing organizations are fine-tuning their operations and taking a proactive role in developing cleaner processes through green lean practices (Singh et al, 2020), lean six sigma (Jamil et al, 2020;Swarnakar et al, 2020) and integrating industry 4.0 into lean production (Tortorella et al, 2020;Yadav et al, 2020). Notwithstanding, various initiatives of LM have widely been adopted in a variety of industries, particularly in developed countries with many successful cases reported in the literature (Pearce et al, 2018).…”
mentioning
confidence: 99%
“…The LM concept we know today consists of indispensable activities applied in the current management and production practices such as automotive, aerospace, furniture manufacturing, textile, process industry and service industry (Kumar and Vinodh, 2020). Due to the foreseen importance of LM, many manufacturing organizations are fine-tuning their operations and taking a proactive role in developing cleaner processes through green lean practices (Singh et al, 2020), lean six sigma (Jamil et al, 2020;Swarnakar et al, 2020) and integrating industry 4.0 into lean production (Tortorella et al, 2020;Yadav et al, 2020). Notwithstanding, various initiatives of LM have widely been adopted in a variety of industries, particularly in developed countries with many successful cases reported in the literature (Pearce et al, 2018).…”
mentioning
confidence: 99%
“…The top management must give continuous and uninterrupted support for the successful implementation of AM by effective knowledge creation and sharing among the workers. It will also motivate the people involved in AM implementation and will make them understand the value of implementation which will ultimately lead to firm competitiveness (Dwivedi et al, 2017;Gaikwad et al, 2020;Singh et al, 2007). Vasanthakumar et al (2016) suggested that information sharing is a necessary factor required for collaborative interorganizational relationships.…”
Section: Top Management Commitmentmentioning
confidence: 99%
“…Ruffo et al (2007) and Oettmeier and Hofmann (2016) summarized significant challenges in the AM implementation concerning supply chain management, logistics and distribution, outsourcing, operations and product design and development. Widespread implementation of AM is not evident in many of the industries because of certain factors which need to be identified and mitigated (Sonar et al, 2020). AM literature reports sector-specific exploratory studies on understanding enablers and barriers of AM implementation such as dentistry (Deradjat and Minshall, 2017), automotive (Dwivedi et al, 2017), small and medium-sized enterprises (SMEs) (Conner et al, 2015) and engineering services (Mellor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are referred to as innovative leaders. Prior studies focused on sustainable leadership and smart working but by now, only a few of them made a direct connection with eco-innovation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the crisis, production should be lean, minimize defects, reduce or eliminate inventories to sustain very productive and cost-efficient organizations [12][13][14]. Furthermore, digital infrastructure, investment in professional qualifications [10,[14][15][16], and mindfulness of the employees is the solution to continue the activity, without health and economic negative consequences.…”
Section: Introductionmentioning
confidence: 99%